Impacts on air dose rates after the Fukushima accident over the North Pacific from 19 March 2011 to 2 September 2015 - Wang, Kuo-Ying; Nedelec, Philippe; Clark, Hannah; Harris, Neil; Kajino, Mizuo; Igarashi, Yasuhito (Public Library of Science (PLoS), 2022)
A fleet of thirteen in-service global container ships continuously measured the air dose rates over the North Pacific after the Fukushima Daiichi Nuclear Power Station (FDNPS) accident. The results showed that the elevated air dose rates over the Port of Tokyo and the FDNPS emissions are significantly correlated (log(emission fluxes) = 54.98 x (air dose rates) (R = 0.95, P-value<0.01), and they are also significantly correlated with the Tsukuba deposition fluxes (log(deposition fluxes) = 0.47 + 30.98 (air dose rates) (R = 0.91, P-value<0.01). These results demonstrate the direct impact of the FDNPS emissions on the depositions of radionuclides and the air dose rates over the Port of Tokyo. Over the North Pacific, the correlation equations are log(emission fluxes) = -2.72 + 202.36 x (air dose rates over the northwestern Pacific) (R = 0.40, P-value<0.01), and log(emission fluxes) = -0.55 + 80.19 x (air dose rates over the northeastern Pacific) (R = 0.29, P-value = 0.0424). These results indicate that the resuspension of the deposited radionuclides have become a dominant source in the transport of radionuclides across the North Pacific. Model simulations show underestimated air dose rates during the periods of 22-25 March 2011 and 27-30 March 2011 indicating the lack of mechanisms, such as the resuspension of radionuclides, in the model.